SHP-1 and IL-1α conspire to provoke neutrophilic dermatoses - Lukens, John R (Landes Bioscience, 2014)
Neutrophilic dermatoses are a spectrum of autoinflammatory skin disorders that are characterized by extensive infiltration of neutrophils into the epidermis and dermis. The underlining biological pathways that are responsible for this heterogeneous group of cutaneous diseases have remained elusive. However, recent work from our laboratory and other groups has shown that missense mutations in Ptpn6, which encodes for the non-receptor protein tyrosine phosphatase Src homology region 2 (SH2) domain-containing phosphatase-1 (SHP-1), results in a skin disease with many of the major histopathological and clinical features that encompass neutrophilic dermatoses in humans. In particular, we found that loss-of-function mutation in Ptpn6 results in unremitting footpad swelling, suppurative inflammation, and neutrophilia. Dysregulated wound healing responses were discovered to contribute to chronic inflammatory skin disease in SHP-1 defective mice and genetic abrogation of interleukin-1 receptor (IL-1R) protected mice from cutaneous inflammation, suggesting that IL-1-mediated events potentiate disease. Surprisingly, inflammasome activation and IL-1β-mediated events were dispensable for Ptpn6(spin)-mediated footpad disease. Instead, RIP1-mediated regulation of IL-1α was identified to be the major driver of inflammation and tissue damage.